Does natural variation in diversity affect biotic resistance?. (14th July 2015) - Harrison, Susan; Cornell, Howard; Grace, James B.; Gibson, David
Summary Theories linking diversity to ecosystem function have been challenged by the widespread observation of more exotic species in more diverse native communities. Few studies have addressed the key underlying process by dissecting how community diversity is shaped by the same environmental gradients that determine biotic and abiotic resistance to new invaders. In grasslands on highly heterogeneous soils, we used addition of a recent invader, competitor removal and structural equation modelling (SEM) to analyse soil influences on community diversity, biotic and abiotic resistance and invader success. Biotic resistance, measured by reduction in invader success in the presence of the resident community, was negatively correlated with species richness and functional diversity. However, in the multivariate SEM framework, biotic resistance was independent of all forms of diversity and was positively affected by soil fertility via community biomass. Abiotic resistance, measured by invader success in the absence of the resident community, peaked on infertile soils with low biomass and high community diversity. Net invader success was determined by biotic resistance, consistent with this invader's better performance on infertile soils in unmanipulated conditions. Seed predation added slightly to biotic resistance without qualitatively changing the results. Soil‐related genotypic variation in the invader also did not affect the results. Synthesis. In natural systems, diversity may be correlated with invasibility and yet have no effect on either biotic or abiotic resistance to invasion. More generally, the environmental causes of variation in diversity should not be overlooked when considering the potential functional consequences of diversity.